Estudantes universitários em contextos emergentes : experiências de participantes da política de ação afirmativa na UFRGS - Erig, Marisa Helena (2016)
Over the last two decades there has been a significant expansion of Brazilian higher education in terms of the following aspects: number of institutions, creation of new courses and higher enrollment rates, as well as higher completion rates. Part of this growth has gone together with general policies in order to promote social inclusion, especially a share of the population historically strange to that educational level. The access democratization has granted students from popular society layers a way in through a policy of quotas at federal institutions and through the program “Universidade para Todos” at private institutions. The present study aimed at investigating the adaptation of such students to university demands, as well as their permanence at those institutions. This study has taken higher education on an affirmative action, the quotas, and students’ permanence in the course at a federal institution (Universidade Federal do Rio Grande do Sul - UFRGS), through a quotas student point of view. The theoretical methodological orientation to analyse UFRGS’s “Programa de Ações Afirmativas” (Affirmative Actions Program) was based on the policy cycle approach: influence context, text production context, and practice context, by Stephen Ball and Richard Bowe. The semi-structured investigation used as a model the principles of discursive textual analysis, and approached emerging categories. The first of them, the student's sociocultural context, revealed the students’ profile as a first generation ones. It has also been observed the students’ and their families’ position toward higher education. When taken into account, educational background, from preparation to the enrollment, permanence willingness, teacher’s influences in the learning process and student’s academic performance, it’s noticeable how challenging it can be for these students to stay at university. Ultimately, this study highlights quotas students’ perceptions on the university’s Affirmative Actions program, thus showing that students understand the quotas program as a way into higher education and as way of social mobility. Nonetheless, these students also related they have suffered veiled discrimination in the academic community due to their quotas access to the university. When evaluating the quotas policy students agree on the need for adjustments to the system, taking into account the quotas student’s profile. As a conclusion we notice students see the quotas policy at university as a way in and also not enough to grant permanence.